Al Tahlîl at Taqābuli fi Al Tasybîh Bayna Lughat Al 'Arabiyah Wa Lughoti Al Indûnisiyah wa Al Istifādah Minhu Ta’lîmiyan - Azhar, Rafif; Syahri, Musta'in; Idris, Nasaruddin; Santoso, Budi (STIQ Amuntai, 2024)
This research aims to determine the similarities and differences between similes in Arabic and Indonesian languages, as well as the lessons learned from this analysis. The research employs a comparative analysis, which involves comparing Arabic similes with Indonesian similes to identify the differences between the two within the science of balaghah. A descriptive approach is adopted for this research. Data collection utilizes documentation and observation instruments, specifically through reviewing journals and books related to tasybih. The study's findings reveal that similes are widely used in both Arabic and Indonesian. However, there are some key similarities and differences between the two languages. Similarities lie in the meaning and function of similes, as they are used as metaphors in poetry and literature. The primary difference lies in the lack of subcategories for similes in Indonesian compared to Arabic. Additionally, the tools used for constructing similes are more extensive in Arabic. Furthermore, similes offer educational benefits in language learning by aiding learners in understanding and memorizing new vocabulary and grammatical structures. This study demonstrates the potential of similes as a tool for teaching both Arabic and Indonesian languages, particularly in enhancing language skills and cultural understanding.